Balloon-assisted peroral cholangioscopy by using an 8.8-mm gastroscope for the diagnosis of Mirizzi syndrome - Azar, Riad (2010)
A 50-year-old woman was referred for treatment of an obstructing gallstone in the common hepatic duct, found on MRCP (A). An ERCP was performed, revealing a 2.5-cm stone obstructing the common hepatic duct (B), with no opacification of the gallbladder. Attempts using mechanical lithotripsy were unsuccessful, so a biliary sphincterotomy was performed, and a 10F plastic stent was placed for temporary decompression. The patient returned 1 week later for cholangioscopy. So that the duct could optimally be visualized, a 0.035-inch guidewire was advanced above the obstructing stone by using a therapeutic duodenoscope (TJF-160VF; Olympus America, Inc, Center Valley, Penn).